Burnout syndrome in nurses/technicians in intensive care units of Clinical Center of Montenegro - Dragana Backović; Dragana Jovanović; Ljubica Pejakov (Биомедицинска истраживања, 2020)
Introduction: The Burnout syndrom is a health issue that greatly disables a person. It includes emotional exhaustion, depersonalization and reduced efficiency in the workplace. So far, this issue has not been addressed where medical staff is concerned. Methods: The Maslach Burnout Inventory - Human Service Survey and Demografic Questionnaire were used. Emotional exhaustion is taken to be the most important aspect of the syndrome. Results: The sample consisted of data acquired from 59 nurses/technicians, out of which 45 were female and 14 male. 12% of them possessed all of the characteristics belonging to the syndrome, 27% of them were overextended (whereby the majority of them were inefficient), while the additional 10% were ineffective. There was a correlation between the chronic disease, on the one hand, and emotional exhaustion (p<0.000) and average ranks of exhaustion scale, on the other hand (p=0.006). Furthermore, there was a significant correlation between reduced efficiency in the workplace and chronic problems (p=0.006). Conclusion: The Burnout syndrome is a multidimensional issue. The method of perceiving the measured dimensions influence the obtained results. The data have shown that the majority of the respondents have some kind of problem concerning their job (burnout, being overextended or ineffective). Significant correlation between chronic disesases and emotional exhaustion underlines the need for further research to benefit the medical staff, as well as health system.
Keywords: Burnout syndrome; intensive care unit; nurses/technicians; Montenegro; chronic diseases